The Implementation of Edmodo-Based Digital Education Application for Elementary School Students’ Learning Interests During the Covid-19 Pandemic - Faridah, Hinda; Suhandi, Andi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Covid-19 has had a massive impact on the educational realm. This article aims to observe students' digitally learning interests based on Edmodo. This research is based on saturated students doing learning online due to the Covid-19 pandemic, marked by parental complaints, decreased participation, and activeness of students in WhatsApp-based online forum activities. The research was conducted online involving 10 students of SD Negeri Sekarwangi based on the assumption that students' interests are heavily influenced by many factors, including the use of media and the selection of learning strategies. Data collection is done through online interviews. Interviews are conducted via private chat, voice calls, and video calls. The research method used is descriptive. The results concluded that 7 out of 10 students felt Edmodo could cope with saturation in distance learning during the Covid-19 pandemic. 7 kids love to use Edmodo because the features are more interesting and can grow enthusiastic. The other 3 students, not interested in using Edmodo because he felt that access was more difficult and complicated.